Os avós e os netos: um encontro de diferentes tempos verbais - Silva, Camila Cuencas Funari Mendes e [UNESP] (2014)
This paper’s goal is the understanding of relations between generations among grandparents and grandchildren over the modern society. Therefore, we have elected Children Literature, particularly stories that treat the themed relation of grandparents and grandchildren, as one of the most various forms of the importance of symbolic exchanges between generations. In this study, we have selected two directed published articles to the children audience: Menina Nina: duas razões para não chorar, from the author Ziraldo (2002) and A menina, o cofrinho e a vovó, from Cora Coralina (2009). We have adopted the psychoanalytic reading as reference for the analysis of selected stories, once that it excels for the individual psychic construction, on its own unconscious conception and its interaction with social and cultural means, which allow us to explore and reflect over the bounds left behind from other generations. During this study at first we discuss about the aging of the world’s population, that comes to nowadays with a percentage in ascension, and yet we reflect regarding the concept of old age. We elected grandparents as one of the representatives of aging in XXI century and, for the eminently age criteria, we pointed out its matter on fulfilling the symbolic and social role that this figures have on their family life. Searching for a link between grandparents and grandchildren, we have found into Children Literature the required input in order to explore this connection, with its own unique way of communication and reflex of various aspects of human subjectivity. Psychoanalytic concepts have shown us that the base for the study of symbolic dimensions of psyche and relations between grandparents and grandchildren generation. With a psychoanalytic point of view, we synthesize our study with analyses of the stories from Ziraldo (2002) and Cora Coralina (2009)...